Flow chemistry : integrated approaches for practical applications - Luis, S. V. (Santíago V.); García-Verdugo, E. (Eduardo) (Royal Society of Chemistry, 2020)
This volume provides an update on recent advances in the field of flow chemistry, with emphasis on new, integrated approaches for green and efficient chemistry.
Includes index.
Keywords: Flow chemistry.; Green chemistry.; Chimie en flux continu.; Chimie verte.; Flow chemistry; Green chemistry